2016
DOI: 10.22160/22035184/aras-2016-37-2/80-106
|View full text |Cite
|
Sign up to set email alerts
|

Sudanese Humanitarian Migrants in Australian Refereed Journals

Abstract: This article reviews the literature about Australian South Sudanese humanitarian migrants in refereed journals, and is underpinned by a concern for the settlement experiences of migrants and the reduced effectiveness of research which is compartmentalised into different academic disciplinary fields. Though a large volume of academic work has paid attention to many themes and issues, the present review identifies gaps in the understanding of Sudanese and South Sudanese views on family violence, economic stress,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…The authors argued that "Blackness is not merely about skin color, but a social construct persistently conceived of as an opposition to whiteness" (p.1). Thus while El-Gack and Yak's (2016; see also Abur and Spaaij, 2016;Wickramaarachchi and Burns, 2016) study found that Sudanese refugees with Australian higher education qualifications are under and unemployed, Colic-Peisker (2005) argued that, as the preferred humanitarian immigrants because of their "whiteness" and "Europeanness", Bosnian [ex-Yugoslavs] refugees were effectively excluded from the 'burden' associated with blackness in Australia. Colic-Peisker asserted that, deemed to have the "right colour", ex-Yugoslav refugees were regarded by the general Australian public to be a good blend into the "White Australian" population and had greater resettlement-potential (2005).…”
Section: Medical Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…The authors argued that "Blackness is not merely about skin color, but a social construct persistently conceived of as an opposition to whiteness" (p.1). Thus while El-Gack and Yak's (2016; see also Abur and Spaaij, 2016;Wickramaarachchi and Burns, 2016) study found that Sudanese refugees with Australian higher education qualifications are under and unemployed, Colic-Peisker (2005) argued that, as the preferred humanitarian immigrants because of their "whiteness" and "Europeanness", Bosnian [ex-Yugoslavs] refugees were effectively excluded from the 'burden' associated with blackness in Australia. Colic-Peisker asserted that, deemed to have the "right colour", ex-Yugoslav refugees were regarded by the general Australian public to be a good blend into the "White Australian" population and had greater resettlement-potential (2005).…”
Section: Medical Literaturementioning
confidence: 99%
“…In their Submission to the Victorian Police Inquiry, the Australian Communities and Foundation Australia and Youth Support Advocacy Service reiterated the racial profiling and criminalisation of Africans in the State of Victoria (Australian Communities and Foundation Australia and Youth Support Advocacy Service, 2013). The African advocacy organisation argued that Blackness is associated with criminal behaviour, resulting in police officers unfairly targeting BAMIA (Wickramaarachchi and Burns, 2016).…”
Section: Criminalisation Of Cald People and Their Suburbsmentioning
confidence: 99%
See 1 more Smart Citation